HER+ interim report for Ethiopia - Endrias, Abrhame; Ketema, Dessalegn; Nchanji, Eileen; Zewdie, Yidnekachew; Roothaert, Ralf; Jaleta, Gemechis (CGIAR System Organization, 2024)
Green Agro-Solution PLC has collaborated with Alliance Bioversity International (CIAT), SNV, and World Veg to offer agricultural services enhanced by digital technologies for vegetable-producing groups in the Welmera and Ejere woredas of the West Showa zone. The project duration spanned from January 1 to June 30, 2024. This interim report provides an overview of the initiative’s major accomplishments for the off-takers and the farmer.